CHANGES IN FISH MERCURY CONCENTRATIONS OVER 20 YEARS IN AN ACIDIFIED LAKE SUBJECT TO EXPERIMENTAL LIMING - Rask M.; Salonen M.; Jones R.I.; Syväranta J.; Järvinen M.; Paloheimo A.; Verta M. (My University, 2007)
Lake Iso Valkjärvi (southern Finland, Europe) was divided in two with a plastic curtain in 1991. One half was neutralized with CaCO3, and the other acted as a control. Mercury concentrations of perch (Perca fluviatilis) and northern pike (Esox lucius) in the limed and control side of the lake were studied both before and after the treatment. Average Hg concentrations of perch and pike were 0.40 and 1.2 μg g-1 (ww) in the early 1980s and 0.25 and 0.72 μg g-1 (ww) a decade later at the time of liming. Ten years after the liming the Hg concentrations of perch in the limed and control sides of the lake were 0.21 and 0.28 μg g-1 (ww) and those of pike were 0.69 and 0.43 μg g-1 (ww), respectively. Nitrogen isotope ratios (δ15N) for perch in the sampling period 2002-2004 showed wide variation suggesting variable trophic positions for individual fish. Pike formed two groups according to their δ15N-values, suggesting that zoobenthos dominated the diet of pike around 20 cm in length and fish that of the larger pikes. Because the δ15N-values of fish were at similar levels in the limed and control sides of L. Iso Valkjärvi, differences in food web structure cannot account for the different fish Hg concentrations. A more likely explanation is water quality induced differences in the dynamics and bioavailability of Hg, leading to decreased formation of methyl Hg. © 2007 Elsevier Ltd. All rights reserved.